(untitled) (Editora Impacto Científico, 2025)
The gut-brain axis is currently extremely important in the research and treatment of certain mental health pathologies. Because they are intrinsically interconnected, they jointly regulate important immunological and psychological functions in the body. Imbalances and alterations in the gut microbiota in humans have been identified in some mental health conditions, such as depression and anxiety disorders. Among the causes contributing to these imbalances are the environment, diet, the use of antibiotics, probiotics, prebiotics, the immune system and genetics. This study aims to shed light on the development and composition of the intestinal microbiota, as well as demonstrating its influence on neuropsychiatric pathologies and possible intervention approaches. An integrative literature review was carried out, based on articles published between 2013 and 2023. DOI: https://doi.org/10.56238/edimpacto2025.090-016